Sustainable management as a dimension of organizational health (Ágora de Heterodoxias, 2023)
The interest of the markets and investors in socially responsible and sustainable companies is being one of the reasons why organizations are raising awareness about the adoption of a management oriented towards sustainability. Aligning management systems with this new market model that tries to balance the triple bottom line - economic-social-ecological - with the interested parties, is becoming an initiative that contributes to not only productivity and financial achievements, but also a factor of competitive advantages for the organization, and an indicator of organizational health. Based on the interpretive and hermeneutical processing of theoretical contributions, documentary information, and empirical references on organizational health and sustainability, this research article aims to show a reflective analysis of how sustainability constitutes a dimension of the organizational health model. The analysis carried out assumed a totalizing vision; and from a process of integration, abstraction and generalization. A combination of research methods and techniques, it shows how through the competitive opportunities of the sustainable management approach, the organization can be oriented towards a culture of leadership and high performance.
Keywords: sustainability; organizational health; competitiveness; management; leadership; high performance culture